(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The Indian auto-components industry has experienced healthy growth over the last few years. Some of the factors attributable to this include a buoyant end-user market, improved consumer sentiment and return of adequate liquidity in the financial system. The revival of the auto industry was initially driven by the fiscal stimulus programme of the government. The data relating to management of working capital of Auto Components industry and its selected units has been collected from the published annual reports of the companies for the year 2014-15to 2017-18.